Priorities and Problems in the Development of Technologies in Education - Sohiba Mirkhayitova; Abbosjon Abrorjonugli Abdullayev (International Journal on Integrated Education, 2022)
Modern technologies in education are considered as a means by which a new educational paradigm can be implemented. Trends in the development of educational technologies are directly related to the humanization of education, which contributes to self-actualization and self-realization of the individual. In modern education, two basic concepts are used: “educational technologies” and “teaching technologies”. The term “educational technologies” is more capacious than “teaching technologies”, since it also implies an educational aspect associated with the formation and development of personal qualities of students.